Hope and community - Nüssel, Friederike (International bulletin of mission research, 2021)
In the final volume of his Constructive Theology, V.-M. Kärkkäinen presents his eschatology and ecclesiology. The approach is grounded in a Trinitarian theology, which explains the interaction of Father, Son, and Holy Spirit as the reason for hope in a new creation. The plausibility of this hope Kärkkäinen explores in light of cosmological scenarios and in comparison with Jewish, Islamic, Buddhist, and Hindu perspectives. Interreligious comparison of sociological models also serves as the starting point for Kärkkäinen’s ecclesiological inquiry. He argues that the church not only has a mission but is mission in its very nature and in ecumenical engagement.
Keywords: Review Article